Does a second resection provide a survival benefit in patients diagnosed with incidental T1b/T2 gallbladder cancer following cholecystectomy?. Issue 2 (February 2017) - Watson, Henry; Dasari, Bobby; Wyatt, Judy; Hidalgo, Ernest; Prasad, Raj; Lodge, Peter; Toogood, Giles
Abstract: Background: Incidental T1b/T2 gallbladder cancers are often managed with a second resection. However it is unclear whether the additional surgical risk is associated with any survival advantage. The aim of this study was to examine the outcomes of patients who underwent a second resection following a diagnosis of incidental T1b/T2 gallbladder cancer. Methods: A retrospective analysis of patients undergoing surgical management following a diagnosis of incidental T1b/T2 gallbladder cancer between 1994 and 2014. Survival outcomes were analysed using the Kaplan–Meier method. Results: Twenty two patients underwent completion surgery following diagnosis of T1b/T2 gallbladder cancer at initial cholecystectomy, 11 of which were found to have residual disease. The presence of residual disease at second surgery in T1b/T2 disease was associated with worse overall survival (residual disease: median survival 12 months, absence of residual disease: median survival not reached, p = 0.025). Conclusion: A significant percentage of patients with T1b/T2 disease have identifiable residual disease following second surgery. Residual disease is associated with poor survival. It is therefore important to inform patients that completion cholecystectomy is primarily performed to inform staging rather than to improve prognosis.